Composite Special Moment Frames - Wide Flange Beam to Concrete-Filled Steel Column Connections - Fischer, Erica; Varma, Amit H; Lai, Zhichao (American Society of Civil Engineers (ASCE), 2020)
This book provides a state-of-the-art overview for designing connections for composite special moment frames (C-SMFs). This book focuses on beam-to-column moment connections for both continuous beam and continuous column connections, and C-SMFs with rectangular or circular concrete-filled tube (CFT) columns. This book will enable engineers to design composite frames more efficiently. It provides an experimental database of 165 tests conducted on beam-to-column connections for C-SMFs, including a summary of the behavior of these connections and an evaluation of these connections using current standard requirements; Design equations for estimating the panel zone shear strength of double split-tee (DST) and through-beam connections; Design examples for DST and through-beam connections; and Flow charts illustrating the design methodology for the connections. This book will be a valuable resource for structural engineers and members of academia.